Bibliometric Analysis: Research Trends in E-Government Implementation - Ismail Nurdin; Abd Salam (Universitas Dharma Wacana, 2022)
This study aims to present the results of a Bibliometric Analysis of research trends related to the implementation of e-government from the Scopus database in 2018-2022. This study uses research methods through Publish or Perish by Harzing on citations in metric form, Microsoft Excel for data frequency analysis, and Vosviewer for data visualization. Findings: Based on the study's results, the research publication on e-government implementation experienced the dynamics of increasing and decreasing. While the number of citations has decreased since 2018, numbered 156 citations. Most cited documents by L.Glyptis (2020) have 40 sources. The most popular keywords include E-Government, Local Government, Critical success factors, Project management, Digital Government, and Public service